Sistem Multi-Sensor Nirkabel Berbasis RFID Untuk Pemantauan Keaktifan Siswa - Zakiah Zakiah; Yuwaldi Away; Fitri Arnia; Andri Novandri (Jurnal Rekayasa Elektrika, 2019)
This study aims to design a multisensor observation system, develop a microcontroller-based prototype with ESP8266 and RFID modules, and analyze the performance of the prototype. From the testing carried out by tagging each time students do activities, the client tag data will be sent to the server, and the results are displayed PLX-DAQ. With the 50 tag cards that have registered the IDs of each student, it shows that those who attend the schedule will be given the logic "1" (otherwise logic "0"), and attendance data will be obtained by calculating the number of attendance of students in four types of activities in four locations. The data is transmitted to Data-loggers through two configurations, namely Data-logger as the client (indirect), and Data-logger as a server (direct). From the two configurations, it was found that the configuration of Data-logger as a server had a performance of 19.08% better than Data-logger as a client. From the data processing, it was found that the highest activity of students was the interest in the activities of language institutions (95.92%), followed by religious activities (95.83%), teaching and earning activities (93.88%), and reading (79.59 %)